The ‘Moving Panorama’ in IIIF. Applications of standards and VR360 techniques in approaching Digital Museography - Stefania De Vincentis; Martin Critelli (Umanistica Digitale)
The scenario of the Italian museums within the IIIF – International Image Interoperability Framework – environment is quite uneven due to a still early stage in the process of digitizing the collections. Nevertheless, the emphasis on the description and interpretation of historical art collections through the framework is relevant to institutions whose environments and connotations are highly decorated. This is the case of the Galleria Borghese of Rome, whose entire collection is constituted not only by single artwork but also by its rooms and walls. In this work, through the examination of the whole artistic heritage of the Galleria Borghese, we aimed to integrate the multiple relationships that occur between rooms and artworks into the IIIF Manifests. To provide the user with a highly immersive experience, we designed Manifests as an interlinked path structured in whole-part relationships. The implementation of VR360 images of the rooms will also be completed to allow visitors to browse between the rooms and the works of art they contain. Finally, to increase the semantic interoperability of the resource within the IIIF Manifest, we decided to apply the VRACore metadata schema. This operation is configured as a first step towards the standardization of information provided by the museum.